A comparative study of social media users’ perception on the Malaysia Airlines Flight MH370 incident in Mainland China and Malaysia - Wang, Changsong; Chen, Yiming; Ahmad, Jamilah (IJCH, 2017)
Abstract—The transformation of online consumer’s behavior is changing landscape of risk and crisis communications. How social media can be a beneficial tool for crisis management? How crisis managers respond to challenges posed by social media? These have become the focus on mobile communication studies. When Malaysia Airlines flight MH370 went missing, the flow of information experienced complexity uncertainty, and ambiguity in terms of information adequacy. The MH370 incident demonstrated an unprecedented international humanitarian response from the technology sector. The authors of this study found that this incident primarily involves attentions from audiences in Malaysia and China respectively. This study attempted to have a deep insight about online users’ perceptions towards the portrait of this incident by the social media in Malaysia and China, and it discovered significant difference of user perception of active social media in these two countries. Social networking sites such as Facebook (in Malaysia), Weibo (in China) and Wechat (in China), become the public opinion field that illustrates sorts of openness and negotiation in Malaysia and China. This research, instead of conventional crisis communication approach, specifically examined active online users in both countries.